Introducing sustainability transitions' thinking in urban contexts. - Frantzeskaki, Niki; Bach, Matthew; Hölscher, Katharina; Avelino, Flor (Springer, 2018)
This chapter describes the basics of transitions thinking, its rationale and relation to sustainability transitions. We outline the fundamental conceptual models and frameworks (multi-phase model, multi-level perspective, multi-path, power and agency) and make a quick introduction to the relation of the sustainability transitions field to environmental governance.
Keywords: Nachhaltige Stadtentwicklung; Methodologie; Bezugssystem; Räumliches Bezugssystem; Stadtgeographie; Stadtsystem; Systemtheorie